Psychological Well-Being as an Independent Predictor of Exercise Capacity in Cardiac Rehabilitation Patients With Obesity - Pietrabissa, Giada; Castelnuovo, Gianluca; Manzoni, Gian Mauro; Cattivelli, Roberto; Molinari, Enrico; Gondoni, Luca Alessandro (Frontiers in Psychology, 2020)
Objective: Exercise capacity (EC) is a well-established predictor of cardiovascular health. It is notoriously influenced by several factors, but the independent effect of psychological well-being (PWB) on EC has not yet been explored. The present study aims to investigate (1) whether PWB is an independent predictor of EC over and above selected demographic, behavioral, and biomedical parameters in a sample of CR patients with obesity and (2) whether PWB is a stronger predictor of EC than the other variables. Methods: Data from 1968 patients were collected at the time of their inclusion in a cardiac rehabilitation (CR) program and retrospectively analyzed in a cross-sectional study. Since cardiorespiratory parameters defined in normal weight populations differ from those of their obese counterparts, an ad hoc validated formula taking body mass index (BMI) into consideration was used to predict EC. Results: A multiple regression analysis revealed left ventricular eject fraction (LVEF) to be the strongest predictor of EC, followed by PWB, type 2 diabetes (DM), smoking status, atrial fibrillation (AF), and education. Bayesian evaluation of informative hypotheses corroborated LVEF as the best predictor of EC, and confirmed the superiority of PWB over and above DM and smoking status in influencing EC. Conclusion: These findings strengthen the link between psychological and physical health, suggesting a better PWB is associated with greater EC. Prompt screening of a patient’s mood and readiness to perform an active lifestyle would therefore enhance the long-term health benefits of CR.